2014
DOI: 10.1152/ajpregu.00046.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for the acceleration of pulmonary V̇o2on-kinetics in humans after prolonged endurance training

Abstract: The effect of prolonged endurance training on the pulmonary V̇O2 on- and off-kinetics in humans, in relation to muscle mitochondria biogenesis, is investigated. Eleven untrained physically active men (means±SD: age 22.4±1.5 years, V̇O2peak 3,187±479 ml/min) performed endurance cycling training (4 sessions per week) lasting 20 wk. Training shortened τp of the pulmonary V̇O2 on-kinetics during moderate-intensity cycling by ∼19% from 28.3±5.2 to 23.0±4.0 s (P=0.005). τp of the pulmonary V̇O2 off-kinetics decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
2
49
1
Order By: Relevance
“…In healthy skeletal muscle, faster V O 2 kinetics after endurance exercise training results primarily from improved oxidative capacity and/or allosteric regulation of mitochondrial respiration (i.e., 1"parallel activation"; Refs. 18,35,36,86,133,207,221,222,242,338,339) (see also Figs. 6 and 7).…”
Section: Muscle V O 2 (V Mo 2 )mentioning
confidence: 96%
“…In healthy skeletal muscle, faster V O 2 kinetics after endurance exercise training results primarily from improved oxidative capacity and/or allosteric regulation of mitochondrial respiration (i.e., 1"parallel activation"; Refs. 18,35,36,86,133,207,221,222,242,338,339) (see also Figs. 6 and 7).…”
Section: Muscle V O 2 (V Mo 2 )mentioning
confidence: 96%
“…These considerable improvements in measures of vascularization and endothelium-dependent vasodilation would improve the surface area for O 2 exchange, which might contribute to absence of an ''overshoot'' in the normalized [HHb]/V O 2 ratio in the trained older compared with the untrained older men. Nevertheless, despite the suggestion that improved O 2 provision to the active tissues plays a critical role in controlling the faster V O 2 kinetics observed in trained older individuals, mechanisms of intracellular control discussed in this review (34,35,40,41,68,88,89) are also to be acknowledged as ''limiting'' factors determining the rate of adjustment of oxidative phosphorylation.…”
Section: Can the Slower V O 2 Kinetics Typically Observed In Older Inmentioning
confidence: 82%
“…Whereas we have suggested that metabolic control regulates V O 2 kinetics in the range of 20 s and that slower V O 2 kinetics may have a limitation in matching of O 2 delivery to the sites of active muscle utilization, Zoladz and colleagues (88) have proposed that muscle V O 2 on-kinetics is mainly controlled/limited by intramuscular factors of metabolic activation. Based on a computer model of oxidative phosphorylation and metabolic control analysis, the increased ATP usage with exercise is accompanied by simultaneous activation of oxidative phosphorylation complexes (including Complexes I, III, IV, ATP/ADP).…”
Section: What Interventions Have Been Shown To Modify the V O 2 Kinetmentioning
confidence: 85%
“…For most of the previous studies, the Oxygen uptake during exercise (Fig.1) has been considered as an exponential function [1]:…”
Section: New Modelling Methods For Vo 2 During Exercisementioning
confidence: 99%
“…Several experiments suggest that oxygen consumption is mainly controlled by intramuscular factor related metabolic system [1], [2]. Unlike heart rate, which is affected by mood, stress, etc., the maximum Oxygen uptake is considered as the most accurate measurement of the fitness of cardiorespiratory system.…”
Section: Introductionmentioning
confidence: 99%